Expansión geográfica y conceptual de la danza Contact Improvisation en España (1990-2000) (Geographic and conceptual expansion of the dance Contact Improvisation in Spain (1990-2000)) - Brozas-Polo, Maria-Paz (Retos, 2016)
El Contact Improvisation es una danza posmoderna de origen estadounidense (1972) con una lenta evolución en España: se inicia en los años 80 en un núcleo catalán y balear y se encuentra aún en periodo de crecimiento. El objetivo de este trabajo es analizar la expansión geográfica de esta danza en los años 90 así como su evolución en el periodo seleccionado. Se trata de un estudio cualitativo donde se combina el análisis de contenido con las comunicaciones personales mediante correspondencia y entrevistas. Los resultados indican que el Contact Improvisation se extiende desde finales de los 80 hacia regiones como Madrid, Andalucía y País Vasco. Se constata como durante su desarrollo se amplía su concepción desde la investigación coreográfica hacia una experiencia aplicable a otros ámbitos artísticos así como educativos y/o terapéuticos. Se da el paso de una danza escénica a una danza social multidireccional. Abstract. Contact Improvisation is a postmodern dance form originating in the USA (1972) which slowly spread and evolved in Spain: it started in the eighties in Catalonia and the Balearic Islands and continues to be in a growth phase. The aim of this paper is to analyse the geographic expansion of this dance in the 90’s and track its evolution during this period. This is a qualitative study combining the analysis of content with personal interviews and mails. The results indicate that from the late 80’s Contact Improvisation extends to regions like Madrid, Andalusia and the Basque Country. During its development it changes from being a choreographic investigation to an experiential one applicable to other areas such as education and/or therapy. It takes a step away from being a stage dance and moves toward a social multidirectional dance.